Abordagens de otimização para apoiar a elaboração e análise de roteiros turísticos - Silva, Admilson Alcantara da (Universidade Federal de São Carlos, 2017)
Considering the tourism policies and their effects in touristic routes, it is important to consider the context in which those routes formed during the development of these itineraries and to take into account similar characteristics of locations and municipalities. In this view, the touristic routes could encourage the discovery of new tourism regions to benefit the local communities, visitors and all organizations directly involved in touristic activity. In this work, we propose a new method based on mathematical programming to support the elaboration and formatting of touristic itineraries considering variables such as profile of visitors, planning of the trip, visitor preferences and nature attractive. Other parameters are also considered such as costs, distances, equipment valuation (museums, churches, fairs and others), services provided to tourists. We also regard several regions available for visits, the various segments of tourism, the various tourists profile and the variation cost/time throughout the seasons/periods of the year. In this proposed method, we apply mathematical models and optimization techniques to maximize the customer´s satisfaction and minimize the costs involved on the touristic routes. To evaluate the potential of the proposed method in practice, it applied in a case study to build routes in the touristic sights of the City of Belém, State of Pará. For the problems modelling and optimization, we used approaches based on the Prize-Collecting Traveling Salesman Problem (PCTSP) and the Traveling Salesman Problem with Priority Prizes (TSPPP) in order to represent appropriately the problem. We are not aware of other works in literature that studied and proposed optimization methods of touristic routes in this research line. In this study, we applied some statistical techniques for the preparation and analysis of data, such as correspondence analysis type and other important techniques to definition and evaluation of the problem and preparation of parameters required by the optimization models. The results showed how the routes could be optimized highlighting the potential of the proposed method to reduce operating costs as well as to maximize the level of the valuation of services offered to tourists. They also contribute to the strengthening of the regional identity and can help to consolidate more satisfactory and competitive tourist itineraries in the tourism market, as well as the expansion and diversification of tourism.
Optimization approaches to support the elaboration and analysis of touristic routes
Enfoques de optimización para apoyar la elaboración y análisis de rutas
Keywords: Otimização de roteiros turísticos; Problema do caixeiro viajante com coleta de prêmios; Problema do caixeiro viajante com prêmios de prioridade; Busca tabu; Análise estatística multivariada; Optimization of touristic routers; Prize-collecting traveling salesman problem; Traveling salesman problem with priority prizes; Tabu search; Multivariate statistical analysis; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL